The Role of GDP Per Capita, HDI, and Industrial Value Added on Carbon Emissions in ASEAN - KHOIRUNNISA, Safira; DEWI, Ditha Dismalasari (Journal of Tourism Economics and Policy, 2025)
Climate change is becoming an increasingly urgent global challenge, with carbon dioxide (CO₂) emissions being the main contributor to the increase in greenhouse gases in the atmosphere. ASEAN countries, face a dilemma between maintaining economic growth and reducing carbon emissions. This study aims to analyze the effect of Gross Domestic Product (GDP), Human Development Index (HDI), and Industrial value added which is Manufacturing Value Added (MVA) on CO₂ emissions in ASEAN during the period 1990–2023. The approach used is panel data regression analysis with a Fixed Effect (FE) model, based on the results of the Chow and Hausman tests as determinants of the best model. The results show that simultaneously, the three independent variables have a significant effect on CO₂ emissions (Prob F = 0.0031). However, partially, only HDI has a positive and significant effect on carbon emissions (p = 0.005), while GDP (p = 0.166) and MVA (p = 0.249) do not show a significant effect. These findings indicate that increased human development has the potential to increase energy consumption and economic activity, which in turn leads to an increase in carbon emissions. Conversely, economic growth and industrial activity in the three countries were not always followed by an increase in emissions, possibly due to economic transformation towards the service sector and the application of more efficient industrial technologies. Therefore, development policies in the ASEAN region need to emphasize the transition to renewable energy, industrial energy efficiency, and strengthening environmental awareness to support the achievement of net-zero emissions.